EVALUASI SENSORI DAN KUALITAS GIZI TORTILA JAGUNG YANG DIPERKAYA DENGAN TEPUNG BIJI KELOR - Nur, Astuti; Sine, Juni Gressilda L.; Nita, Maria Helena Dua (Research and Community Service Unit, Poltekkes Kemenkes Kupang, 2022)
One of the agricultural product processing industries currently being developed in East Nusa Tenggara is corn. Corn has a relatively high nutritional content, thus it possesses economic value for the community. One of the snack products from corn is tortilla. The tortillas can be modified with other food ingredients that contain good nutrition to increase its nutritional value. Moringa seeds contain carbohydrates, fats and proteins. Hence, moringa seeds can be an alternative food source of a new protein which is able to overcome protein deficiency, particularly in East Nusa Tenggara. The experiment was designed by Completely Randomized Design (CRD) with several formulas for substitution of corn flour with moringa seed flour, which were: P1 (100%: 0%), P2 (95%:5%), P3 (90%:10%), and P4 (85%:15%). An organoleptic test was administered to determine the panelists' preference for tortilla formulas and a proximate test to examine the nutritional value of tortillas. The results of the organoleptic test revealed that corn tortilla substituted with moringa seed flour up to 20% owned a significant effect on the color, aroma, taste and texture of the tortilla with a p-value <0.05. The proximate test results presented that tortillas with moringa seed flour substitution possessed a significant effect on protein, fat, carbohydrate, water, ash and fibre content of tortilla with a p-value <0.05.